The influence of absolute minimum (l1–δ1) type inversion on the ionization energy of the ground state of shallow donors in n-Ge single crystals - Луньов, Сергій Валентинович (Eastern-European Journal of Enterprise Technologies, 2014)
Based on the Ritz variational method and perturbation theory, ionization energy of shallow donors for the cases of L1 and Δ1 model of the conduction band of germanium single crystals was calculated. It was shown that the absolute minimum (L1–Δ1) type inversion in n-Ge leads to a significant increase in ionization energy of shallow donors. Using the Ritz variational method allows more accurately describe the experimental results with respect to the calculation based on perturbation theory. Comparison of theoretical calculations with experimental data shows that the hydrogenlike impurity model is approximate and may be used only for Sb impurity in germanium. For impurities, such as, P and As chemical shift, that is "personality" of the ion field potential of each impurity, which is not Coulomb must be considered.